Electron-impact excitation of argon: cross sections of interest in plasma modeling - Gangwar, Reetesh Kumar; Sharma, Lalita; Srivastava, Rajesh; Stauffer, Allan D. (Physical review. A, Atomic, molecular, and optical physics, 2010)
We used the relativistic distorted-wave approximation to calculate the excitation of Ar from its ground-state 3p6 configuration to the higher lying fine-structure levels of the 3p53d, 3p55s, and 3p55p manifolds. The calculation has been performed with relativistic Dirac-Fock multiconfiguration wave functions for the ground and excited states. Results for the differential and integrated cross sections are obtained at energies in the range up to 100 eV, and these are compared with available experimental measurements and earlier theoretical nonrelativistic distorted-wave and R-matrix calculations. Analytic fits to our integrated cross sections are provided.
Gesehen am 25.07.2023